FAKTOR-FAKTOR YANG MEMPENGARUHI AKUNTABILITAS KINERJA - Anik Irawati; Caesar Agesta (Universitas Bandar Lampung (UBL), 2019)
This research was aimed to prove empirically the effect of the budget target clarity, the accounting control, the public accounting implementation, the laws and regulations obedience, and the reporting system on the performance accountability of OPD in Bandar Lampung. The sampling technique used in this research was the purposive sampling. A number of samples used in this research were 93 respondents (employees who handled finances at OPD). The data analysis technique used in this research was the structural equal model analysis. The data analysis technique used in this research was the PLS program. The result of this research showed that the budget target clarity, the public accounting implementation, the laws and regulation obedience, and reporting systems had a significant and positive effect on the performance accountability of government agencies; moreover, the accounting control did not have a significant and positive effect on the performance accountability.